Highly efficient air-stable colloidal quantum dot solar cells by improved surface trap passivation. (September 2017) - Azmi, Randi; Sinaga, Septy; Aqoma, Havid; Seo, Gabsoek; Ahn, Tae Kyu; Park, Minsuk; Ju, Sang-Yong; Lee, Jin-Won; Kim, Tae-Wook; Oh, Seung-Hwan; Jang, Sung-Yeon
Abstract: While the power conversion efficiency (PCE) of colloidal quantum dot (CQD) solar cells can reach > 10%, the major obstacle for charge extraction and energy loss in such devices is the presence of surface trap sites within CQDs. In this work, highly trap-passivated PbS CQDs were developed using a novel iodide based ligand, 1-propyl-2, 3-dimethylimidazolium iodide (PDMII). We examined the effects of PDMII on the surface quality of PbS-CQDs and compared them with TBAI, which is the best-selling iodide based ligand. By using PDMII, improved surface passivation with reduced sub-bandgap trap-states compared to TBAI was achieved. The reduced trap density resulted in enhanced charge extraction with diminished energy loss (0.447 eV) in the devices. Solar cell devices using our PDMII based CQDs displayed high PCE and air stability. The certified PCE of our PDMII based devices reached 10.89% and was maintained at 90% after 210 days of air storage. Graphical abstract: Highly passivated PbS CQDs were developed using a novel iodide based ligand, 1-propyl-2, 3-dimethylimidazolium iodide (PDMII). The effects of PDMII on the surface quality of PbS-CQDs were investigated. By using PDMII, improved surface passivation with reduced sub-bandgap trap-states was achieved. Solar cell devices using our PDMII based CQDs displayed state-of-the-art PCE (10.99%) and air stability with low energy loss (0.447 eV). Highlights: High efficiency colloidal quantum solar cells (10.99%) using iodide-exchanged quantum dots. Efficient reduction of surface trap-states of quantum dots using novel iodide source, PDMII. Unprecedentedly high air stability of devices due to improved surface passivation. Exceptionally low energy loss in devices using PDMII-exchanged quantum dots.